The tibial nerve compression test for the diagnosis of lumbar spinal canal stenosis—A simple and reliable physical examination for use by primary care physicians - Shu Adachi; Atsushi Nakano; Akihiro Kin; Ichiro Baba; Yoshitaka Kurokawa; Masashi Neo (Acta Orthopaedica et Traumatologica Turcica, 2018)
Objectives: In the present study, we aimed to evaluate the diagnostic accuracy and suitability of the ‘Tibial Nerve Compression Test (TNCT)’ as a screening tool for lumbar spinal canal stenosis (LSS). Methods: A total of 108 consecutive patients admitted to our hospital for surgical treatment or diagnosis of LSS were included in this study. Fifty healthy volunteers were examined as a control group. The severity of tenderness was scored (tenderness score) and measured on a visual analogue scale (P-VAS score). These scores were compared between the LSS and control groups. Moreover, they were compared before and after the operation among operated patients. Results: The positive tenderness rate was significantly higher (92.6% [100/108]) in the LSS group than in the control group (30% [15/50]). The sensitivity and specificity of TNCT (95% confidence interval) were 0.93 (0.88–0.96) and 0.70 (0.61–0.77), respectively. Positive tenderness rates and P-VAS scores were significantly higher in the LSS group (p < 0.0001). Scores on all measures significantly improved post-operatively in operated patients (p < 0.0001). Conclusion: The Tibial Nerve Compression Test is a useful screening tool for LSS diagnosis in a primary care setting. Level of evidence: Level II, diagnostic study Keywords: Tibial nerve compression test, Lumbar spinal canal stenosis, Diagnostic accuracy, Visual analog scale, Clinical examination test